Conference Scene: Oslo Epigenetics Symposium 2012. (February 2013) - Collas, Philippe; Eskeland, Ragnhild
The Oslo Epigenetics Symposium 2012 held in Oslo, Norway, brought together ten speakers from several European countries and the USA for an evening public lecture and a full day of presentations on emerging topics in the field of epigenetics, gene regulation and organization of the cell nucleus.